Absolute age evidence of Early to Middle Ordovician volcanism in Peninsular Malaysia - Quek, Long Xiang; Ghani, Azman Abd; Lai, Yu Ming; Lee, Hao Yang; Saidin, Mokhtar; Roselee, Muhammad Hatta; Badruldin, Muhammad Hafifi; Hassan, Meor Hakif Amir; Abdul Aziz, Jasmi Hafiz; Ng, Tham Fatt; Ali, Muhammad Afiq Muhammad; Zulkifley, Mohamad Tarmizi Mohamad (Indian Academy of Sciences, 2018)
Evidence of Early Palaeozoic volcanism in Peninsular Malaysia is largely represented by felsic Gerik- Dinding meta-volcanic rocks; however, reliable absolute ages for the meta-volcanic rocks are still lacking. This restricts correlation of these meta-volcanic rocks with other Early Palaeozoic East Gondwana Proto- Tethys margin tectonic elements identified in the evolution of Southeast Asia. Here, we report petrographic data and zircon U-Pb age of the Gerik-Dinding metavolcanic rocks. Zircons from three Gerik-Dinding meta-volcanic rock samples yield Early to Middle Ordovician weighted mean 206Pb/238U ages between 480 and 460 Ma. The formation age of the meta-volcanic rocks coincides with the post-collision stage from the final amalgamation of Asian micro-continental fragments with the East Gondwana Proto-Tethys margin. Tectonic processes such as lithospheric delamination during the post-collision period could have induced the hot asthenosphere to underplate the continental crust and trigger crustal anatexis. With these findings, the Early Palaeozoic tectonic history of Peninsular Malaysia needs careful review.